RACK1 may participate in placental development at mid‐gestation via regulating trophoblast cell proliferation and migration in pigs. Issue 4 (13th March 2023) - Wu, Zhimin; Hu, Guangling; Gong, Ting; Hu, Qun; Hong, Linjun; Zhang, Yiyu; Ao, Zheng
Abstract: Intrauterine growth restriction (IUGR) is a severe complication in swine production. Placental insufficiency is responsible for inadequate fetal growth, but the specific etiology of placental dysfunction‐induced IUGR in pigs remains poorly understood. In this work, placenta samples supplying the lightest weight (LW) and mean weight (MW) pig fetuses in the litter at Day 65 (D65) of gestation were collected, and the relationship between fetal growth and placental morphologies and functions was investigated using histomorphological analysis, RNA sequencing, quantitative polymerase chain reaction, and in vitro experiment in LW and MW placentas. Results showed that the folded structure of the epithelial bilayer of LW placentas followed a poor and incomplete development compared with that of MW placentas. A total of 654 differentially expressed genes (DEGs) were screened out between the LW and MW placentas, and the gene encodes receptor for activated C kinase 1 (RACK1) was found to be downregulated in LW placentas. The DEGs were mainly enriched in translation, ribosome, protein synthesis, and mammalian target of rapamycin (mTOR) signaling pathway according to gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. In vitro experiments indicated that the decreased RACK1 in LW placentas may be involved in abnormal development of placental folds (PFs) by inhibiting the proliferation and migration of porcine trophoblast cells. Taken together, these results revealed that RACK1 may be a vital regulator in the development of PFs via regulating trophoblast cell proliferation and migration in pigs.